2008
DOI: 10.1016/j.yjmcc.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Systems approaches to preventing transplanted cell death in cardiac repair

Abstract: Stem cell transplantation may repair the injured heart, but tissue regeneration is limited by death of transplanted cells. Most cell death occurs in the first few days post-transplantation, likely from a combination of ischemia, anoikis and inflammation. Interventions known to enhance transplanted cell survival include heat shock, over-expressing anti-apoptotic proteins, free radical scavengers, anti-inflammatory therapy and co-delivery of extracellular matrix molecules. Combinatorial use of such interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
298
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(312 citation statements)
references
References 103 publications
11
298
1
2
Order By: Relevance
“…To rapidly determine whether human cardiac tissue patches could engraft in muscle in vivo, we established a model of patch transplantation into skeletal muscle. Our previous work with direct injection of enzymatically dispersed cells demonstrated that death of cells during transplantation was multifactorial and that a ''cocktail'' of prosurvival interventions was required to achieve engraftment (1,18). Patches containing 3 ϫ 10 6 human cardiomyocytes cultured in the optimal RPMI-B27 media were therefore heat shocked 1 day before transplantation, bathed in prosurvival cocktail, and then implanted into the skeletal muscle of nude rats.…”
Section: Patches Containing Only Cardiomyocytes Do Not Form Substantialmentioning
confidence: 99%
“…To rapidly determine whether human cardiac tissue patches could engraft in muscle in vivo, we established a model of patch transplantation into skeletal muscle. Our previous work with direct injection of enzymatically dispersed cells demonstrated that death of cells during transplantation was multifactorial and that a ''cocktail'' of prosurvival interventions was required to achieve engraftment (1,18). Patches containing 3 ϫ 10 6 human cardiomyocytes cultured in the optimal RPMI-B27 media were therefore heat shocked 1 day before transplantation, bathed in prosurvival cocktail, and then implanted into the skeletal muscle of nude rats.…”
Section: Patches Containing Only Cardiomyocytes Do Not Form Substantialmentioning
confidence: 99%
“…Scaffolds may promote oriented tissue architectures that facilitate diffusion-based mass transfer to reduce the ischemic injury often encountered in cell aggregates or cell transplantation (9). A scaffold can also promote survival and integration by enhancing neovascularization while minimizing fibrotic encapsulation (10).…”
mentioning
confidence: 99%
“…Here we show, for the first time, that graft architecture can be highly variable at the time of transplantation, which could represent a considerable source of treatment variation among recipients and across the fundus. In this regard, bimodal imaging allows for early detection of a central problem inherent to cellsuspension therapeutics: undesired graft aggregation resulting in ischemia (reviewed by Robey et al 26 ) and/or spatial inhibition of functional connections, such as the highly limited contact observed between bolus PPC-grafts and host RPE 9 -a common architecture seen here and in other studies 7,9,27 ). Conversely, bimodal imaging can also detect extensive graft dispersion, which can leave insufficient density of cells for functional benefit, as small quantities of integrating PPCs are unlikely to rescue vision.…”
Section: Real-time Detection Of Graft Placement and Survivalmentioning
confidence: 60%